2017
DOI: 10.3892/mmr.2017.7238
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates generalized hyperalgesia in mice with induced adenomyosis

Abstract: Adenomyosis is a common gynecologic disorder characterized by the presence of endometrial glands and stroma within the myometrium. The present study investigated the effect of quercetin in neonatal Imprinting Control Region mice with tamoxifen-induced adenomyosis. The body weight and hotplate response latency of all mice was examined at 4, 8, 12 and 16 weeks after birth. The mice dosed with tamoxifen were divided into four groups: high- or low-quercetin group, valproic acid (VPA) group and untreated group. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Moreover, the reduced levels of these proteins are more significant in EESCs compared with EuESCs. Notably, these results are consistent with a recent study 26 showing that oral treatment of quercetin significantly inhibited the infiltration of myometrium induced by tamoxifen in neonatal mice. Up to date, several Chinese herbs such as berberine and tanshinone IIA have been reported to inhibit the growth, invasion and migration through regulating NF-κB/p65, 39 LPS/TLR4, 40 and 14-3-3ζ signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the reduced levels of these proteins are more significant in EESCs compared with EuESCs. Notably, these results are consistent with a recent study 26 showing that oral treatment of quercetin significantly inhibited the infiltration of myometrium induced by tamoxifen in neonatal mice. Up to date, several Chinese herbs such as berberine and tanshinone IIA have been reported to inhibit the growth, invasion and migration through regulating NF-κB/p65, 39 LPS/TLR4, 40 and 14-3-3ζ signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are not in accordance with a previous study based on animal models. 26 Specifically, Nie et al 26 demonstrated that intragastric administration of quercetin caused no significant body weight loss in neonatal Imprinting Control Region (ICR) mice induced with adenomyosis compared with the untreated control group. However, this result found by Nie et al may be due to a pain-suppressed behavior and concomitant-reduced food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the ability of this | 5923 combination of dietary supplements to decrease PGE2 levels could justify the clinical effects seen in the patients at the end of the treatment. Nevertheless, it must be also considered the recent observation that treatment with quercetin improves the generalized hyperalgesia in an animal model of adenomyosis (Nie & Liu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin, reduces local estrogen by reducing FSH and LH (animal model studies), and reduces VEGF (Massi et al, 2017). Moreover, it has recently been demonstrated that quercetin decreases the incidence of hyperalgesia in mice with experimental adenomyosis through the reduction of central sensitization and this could be a promising treatment for adenomyosis (Nie & Liu, 2017).…”
Section: Introductionmentioning
confidence: 99%